Increased Frequency of CD4+ CD25+ FoxP3+ T Regulatory Cells in Pulmonary Tuberculosis Patients Undergoing Specific Treatment and Its Relationship with Their Immune-Endocrine Profile - Ariana Díaz; Natalia Santucci; Bettina Bongiovanni; Luciano D’Attilio; Claudia Massoni; Susana Lioi; Stella Radcliffe; Griselda Dídoli; Oscar Bottasso; María Luisa Bay (Journal of Immunology Research)
Tuberculosis (TB) is a major health problem requiring an appropriate cell immune response (IR) to be controlled. Since regulatory T cells (Tregs) are relevant in IR regulation, we analyzed Tregs variations throughout the course of TB treatment and its relationship with changes in immune-endocrine mediators dealing with disease immunopathology. The cohort was composed of 41 adult patients, 20 of them completing treatment and follow-up. Patients were bled at diagnosis (T0) and at 2 (T2), 4 (T4), 6 (T6), and 9 months following treatment initiation. Twenty-four age- and sex-matched healthy controls (HCo) were also included. Tregs (flow cytometry) from TB patients were increased at T0 (versus HCo P<0.05), showing even higher values at T2 (versus T0 P<0.01) and T4 (versus T0 P<0.001). While IL-6, IFN-γ, TGF-β (ELISA), and Cortisol (electrochemiluminescence, EQ) were augmented, DHEA-S (EQ) levels were diminished at T0 with respect to HCo, with cytokines and Cortisol returning to normal values at T9. Tregs correlated positively with IFN-γ (R=0.868, P<0.05) at T2 and negatively at T4 (R=-0.795, P<0.05). Lowered levels of proinflammatory cytokines together with an increased frequency of Tregs of patients undergoing specific treatment might reflect a downmodulatory effect of these cells on the accompanying inflammation.